2007
DOI: 10.1002/mrc.2126
|View full text |Cite
|
Sign up to set email alerts
|

Long-range19F15N distance measurements in highly-13C,15N-enriched solid proteins with19F-dephased REDOR shift (FRESH) spectroscopy

Abstract: We present a novel rotational-echo double resonance (REDOR) method for detection of multiple (19)F-(15)N distances in solid proteins. The method is applicable to protein samples containing a single (19)F label, in addition to high levels of (13)C and (15)N enrichment. REDOR dephasing pulses are applied on the (19)F channel during an indirect constant time chemical shift evolution period on (15)N, and polarization is then transferred to (13)C for detection, with high-power (1)H decoupling throughout the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 32 publications
(64 reference statements)
0
26
0
Order By: Relevance
“…This technique is a well-established tool in structural biology, and can measure distances with a resolution that rivals X-ray crystallography. (40) The shortest interdimer distance between 13 C- and 19 F-containing residues is remarkably short in the trimer-of-dimers structure (5.6 Å, see Figure 2B) and substantially longer in the hedgerow structure (8.0 Å). In both cases the interdimer distances are shorter than the shortest likely 13 C to 19 F distance within a dimer (8.8 Å in 1qu7), so the REDOR dephasing will be dominated by the interdimer interaction.…”
Section: Resultsmentioning
confidence: 89%
“…This technique is a well-established tool in structural biology, and can measure distances with a resolution that rivals X-ray crystallography. (40) The shortest interdimer distance between 13 C- and 19 F-containing residues is remarkably short in the trimer-of-dimers structure (5.6 Å, see Figure 2B) and substantially longer in the hedgerow structure (8.0 Å). In both cases the interdimer distances are shorter than the shortest likely 13 C to 19 F distance within a dimer (8.8 Å in 1qu7), so the REDOR dephasing will be dominated by the interdimer interaction.…”
Section: Resultsmentioning
confidence: 89%
“…Although the simplest way to overcome these complications is to simplify the experimental system to an isolated spin pair, either by sparse/specific isotopic labeling [6668], dilution of labeled molecules in natural abundance [37], or specific incorporation of fluorinated probes either by attaching through a disulfide linkage [69] or biosynthetically as a non-natural amino acid [70], we were motivated to identify an approach applicable to 31 P-dephased REDOR of crystalline compounds, for which these strategies are not an option. Several studies have reported treatments of REDOR dephasing for multispin systems [7174].…”
Section: Resultsmentioning
confidence: 99%
“…57-59 For example, distances between distinct 13 C atoms could be probed within the organic phase in enriched bone using standard DARR (Dipolar Assisted Rotational Resonance) and/or PDSD experiments (Proton Driven Spin Diffusion), 60,61 whereas distances between the organic and mineral components could potentially be measured using derivatives of the REDOR and TEDOR (Transferred Echo Double Resonance) experiments that can detect weak couplings in the presence of strong couplings, and can even use the strong couplings for enhanced spectral resolution. 62,63 Even at ∼20% 13 C enrichment, a ∼20 fold increase in NMR signal intensity would be realized in a 1D 13 C spectrum (leading to ∼400 fold decrease in experimental time for equivalent signal to noise ratio) relative to a sample at natural abundance, and provide adequate spin densities to enable most advanced multidimensional experimental techniques.…”
Section: Perspective: Study Of Low-abundance Amino Acids In Bonementioning
confidence: 99%